Elements of the philosophy of right - Hegel, Georg Wilhelm Friedrich, 1770-1831; Wood, Allen W.; Nisbet, H. B. (Hugh Barr) (Cambridge : Cambridge University Press, 1991)
This book is a translation of a classic work of modern social and political thought, Elements of the Philosophy of Right. Hegel's last major published work, is an attempt to systematize ethical theory, natural right, the philosophy of law, political theory and the sociology of the modern state into the framework of Hegel's philosophy of history. Hegel's work has been interpreted in radically different ways, influencing many political movements from far right to far left, and is widely perceived as central to the communication tradition in modern ethical, social and political thought. This edition includes extensive editorial material informing the reader of the historical background of Hegel's text, and explaining his allusions to Roman law and other sources, making use of lecture materials which have only recently become available. The new translation is literal, readable and consistent, and will be informative and scholarly enough to serve the needs of students and specialists alike.
Title from publisher's bibliographic system (viewed on 13 May 2019).
Keywords: elektronické knihy; electronic books; Law -- Philosophy; Natural law; State, The; Political science; Ethics